Self-concepts and demographic characteristics of battered women in Gauteng, South Africa - E.S. Idemudia (AOSIS, 2009)
In South Africa, studies have shown that one in every four women are abused or battered. Put graphically, 25% of women in the Republic of South Africa (RSA) are assaulted by their boyfriend/partner or husband and a woman suffer battering on average of 39 times before she seeks outside help. Woman battering can leave women abused, distressed, create fear, limits behaviour, cause psychological damage and physical harms and very often breaks down self-esteem and leaves the individual self-incompetent. Hence the need to understand how women who have been abused rate their pre and post abuse self-concepts, how their demographic characteristics influence their self-concepts and also understand their attitude towards their abuser.